2023
DOI: 10.1038/s41598-023-28417-2
|View full text |Cite
|
Sign up to set email alerts
|

A study of management decisions to adopt emission reduction measures in heavy industry in an emerging economy

Abstract: Heavy industry can face challenges in choosing applicable climate change mitigation measures due to a lack of technical background and practical guidance. A better understanding of these determinants is needed to design region-specific climate policies that most effectively enable more ‘successful’ low carbon transitions. Set in an emerging economy, this study aims to understand the determinants which underlie investment decision-making in greenhouse gas reduction. It relies on empirical research using an expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 64 publications
(113 reference statements)
0
2
0
1
Order By: Relevance
“…Literature review showed that there were industries viz. cement [26]- [34], agriculture [13], [14], [35]- [39], energy [40], mining [41], [42], paper and pulp [44]- [45], iron and steel [7], [46]- [52], plastic [53], dairy [54], manufacturing [49], gas industry [45], [55]- [60], finance [61], [62], forest [63]- [67], water industry [68], wind power [69], pharmaceutical [70], chemical [71], [72], apparel [73], hospitability [74], construction [75], [76], cleantech [77] and real estate [78] were identified from the literature review. Amongst the listed strategies, many were repetitive which pointed to their high demand in the today's date, like fuel replacement wherein liquified natural gas will be used in place of coal, bioenergy in conjunction with carbon capture and storage [7],…”
Section: Mapping and Analysing Ccmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature review showed that there were industries viz. cement [26]- [34], agriculture [13], [14], [35]- [39], energy [40], mining [41], [42], paper and pulp [44]- [45], iron and steel [7], [46]- [52], plastic [53], dairy [54], manufacturing [49], gas industry [45], [55]- [60], finance [61], [62], forest [63]- [67], water industry [68], wind power [69], pharmaceutical [70], chemical [71], [72], apparel [73], hospitability [74], construction [75], [76], cleantech [77] and real estate [78] were identified from the literature review. Amongst the listed strategies, many were repetitive which pointed to their high demand in the today's date, like fuel replacement wherein liquified natural gas will be used in place of coal, bioenergy in conjunction with carbon capture and storage [7],…”
Section: Mapping and Analysing Ccmsmentioning
confidence: 99%
“…It has been reported that an integrated process involved in green cement production can help to minimize the environmental influence of the cement industry's activity without compromising reliability, quality, cost, performance [111]. In case of paper and pulp industry, speculated technologies to increase the efficiency of paper and pulp industry include black liquor gasification and efficient drying technology and operational commitment from top management [44].…”
Section: Mapping and Analysing Ccmsmentioning
confidence: 99%
“…Para analizar la sostenibilidad ambiental de las fuentes energéticas en las industrias manufactureras del Ecuador, se utiliza términos monetarios como: el gasto e inversión que realizan dichas empresas en las actividades económicas para reducir los gases de efecto invernadero (Oswald, 2017). Es por ello, que para el cuidado del ambiente se requiere de inversión, la cual refleje resultados a largo plazo al momento de realizar un gasto óptimo al implementar una nueva tecnología (Soaloon et al, 2023). De esta manera, la racionalidad económica tiene como objetivo, obtener un gasto productivo y mayor beneficios por medio de la inversión, tanto en bienes y servicios para reducir el efecto invernadero (Hernández, 2010).…”
Section: Introductionunclassified